ANALISIS GARIS SEMPADAN BANGUNAN PADA BANGUNAN BERTINGKAT: Analysis of Building Boundary Lines in Multi-Storey Buildings - Hniki Rym Marissa; Meta Indah Budhianti (Reformasi Hukum Trisakti, 2025)
Many multi-storey buildings in the Special Capital Region of Jakarta have been constructed in violation of building setback lines, resulting in conflicts with surrounding communities. The issues examined in this study are: how is the regulation of building setback lines for multi-storey buildings in Jakarta governed under Regional Regulation Number 7 of 2010, Regional Regulation Number 1 of 2014, and Governor Regulation Number 128 of 2012? and what measures have been taken by the Provincial Government of Jakarta to address violations of these setback line regulations? The legal research method used is normative juridical research with a descriptive approach, relying on secondary data analyzed qualitatively. Based on the discussion, it is concluded that non-compliance with building setback lines in multi-storey buildings in Jakarta has led to conflicts that negatively affect the surrounding communities. The provisions set forth in Regional Regulation Number 7 of 2010, Regional Regulation Number 1 of 2014, and Governor Regulation Number 128 of 2012 have not been effectively enforced. Therefore, enhanced legal enforcement efforts, oversight, and coordination among relevant stakeholders are required to halt ongoing violations and prevent further losses.